Standing Waves of the Coupled Nonlinear Schrödinger Equations (Analysis in Theory and Applications, 2014)
In this paper, we study the existence of standing waves of the coupled nonlinear Schrödinger equations. The proofs of which rely on the Lyapunov-Schmidt methods and contraction mapping principle are due to F. Weinstein in [1].
Keywords: Coupled nonlinear Schrödinger equations; Lyapunov-Schmidt; contraction mapping principle.